The Influence of Product Quality, Word of Mouth, and Location on Consumer Purchase Interest - M Syarifuddin Rosyid; Joko Suyono; Damasari Ratnasahara Elisabeth (LPPM of NAROTAMA UNIVERSITY, 2019)
Purpose: Therefore this study is intended to analyze whether product quality, word of mouth, and location can influence consumers buying interest to buy UKM product Design/methodology/approach: This research is quantitative study Findings: The result showed that the three hypotheses proposed had a significant and supported. Research limitations/implications: This research is quantitative study with a sample of 190 respondentS IN wedoro Village Practical implications: The result showed that the three hypotheses proposed had a significant and supported. Paper type: This paper can be categorized as case study paper